PERIZINAN USAHA LAUNDRY SEBAGAI UPAYA PENCEGAHAN PENCEMARAN LINGKUNGAN - Dani Elsadai Figenius (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
Licensing is one of the important factors for environmental control of waste that has the risk of polluting the environment. Along with the development of increasingly sophisticated technology, many new business ventures have emerged. These business enterprises, of course, need to obtain a business permit from the local government. One of the businesses that the community likes is the laundry business. Laundry businesses need to have a permit, this is because a business needs to obtain a permit from the government, so that the business can be officially registered. The use of secondary data by means of addition, the analysis of informative qualitative methods, the presentation of idata based on a theoretical framework, and the understanding in the qualitative method, the normative juridical approach, the statutory approach, and the presentation with the specification of descriptive research in interpreting the data are the research methods that will be used. Ilaundry businesses must have a permit. The importance of obtaining permits for this laundry business is because it is related to the waste that is disposed of, because in its operational operations, a lot of laundry businesses use chemical additives. For this reason, a laundry business needs to have a permit from the government. In addition to having to comply with government regulations related to laundry business licenses, the in-laws doing the laundry business also have to comply with environmental permits and permits for disposal of laundry waste. This disposal permit cannot be separated from a business permit. because the laundry business itself has risks that are quite large, the impact on the environment. Businesses that have risk must comply with applicable regulations, namely Government Regulation Number 15 of 2021 concerning Implementation of Risk-Based i-Business Licensing